Lifetime prediction of components for reuse: an overview - Kara, S.; Mazhar, Muhammad Ilyas; Kaebernick, H. (Inderscience Publishers, 2004)
A state-of-the-art prediction of the remaining life of a product is discussed in detail in this paper on the basis of a literature study. The objective is to develop a robust model for estimating the remaining life of a product on the basis of data collected during its operating life. Very little research has been devoted to the remaining life prediction as a whole, but most research has been focused on predicting the mean time between failures (MTBF) and/or mean time to failure (MTTF). The authors of this paper have gathered this information to reflect the nature of the work of researchers to date and use it as a basis for model development.